Understanding the Full Spectrum of Organ Injury Following Intrapartum Asphyxia - LaRosa, Domenic A.; Ellery, Stacey J.; Walker, David W.; Dickinson, Hayley (Frontiers in Pediatrics, 2017)
Birth asphyxia is a significant global health problem, responsible for ~1.2 million neonatal deaths each year worldwide. Those who survive often suffer from a range of health issues including brain damage - manifesting as cerebral palsy (CP) - respiratory insufficiency, cardiovascular collapse and renal dysfunction, to name a few. Although the majority of research is directed towards reducing the brain injury that results from intrapartum birth asphyxia, the multi-organ injury observed in surviving neonates are of equal importance. Despite the advent of hypothermia therapy for the treatment of hypoxic-ischemic encephalopathy (HIE), treatment options following asphyxia at birth remain limited, particularly in low-resource settings where the incidence of birth asphyxia is highest. Furthermore, although cooling of the neonate results in improved neurological outcomes for a small proportion of treated infants, it does not provide any benefit to the other organ systems affected by asphyxia at birth. The aim of this review is to summarise the current knowledge of the multi-organ effects of intrapartum asphyxia, with particular reference to the findings from our laboratory using the precocial spiny mouse to model birth asphyxia. Furthermore, we reviewed the current treatments available for neonates who have undergone intrapartum asphyxia, and highlight the emergence of maternal dietary creatine supplementation as a preventative therapy, which has been shown to provide multi-organ protection from birth asphyxia-induced injury in our preclinical studies. This cheap and effective nutritional supplement may be the key to reducing birth asphyxia-induced death and disability, particularly in low-resource settings where current treatments are unavailable.